2020
DOI: 10.3390/foods9020192
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Variability in Flow and Viscoelastic Behavior of Levan Produced by Gluconobacter albidus TMW 2.1191

Abstract: Levan is a fructan-type exopolysaccharide which is produced by many microbes from sucrose via extracellular levansucrases. The hydrocolloid properties of levan depend on its molecular weight, while it is unknown why and to what extent levan is functionally diverse depending on its size. The aim of our study was to gain deeper insight into the size-dependent functional variability of levan. For this purpose, levans of different sizes were produced using the water kefir isolate Gluconobacter albidus TMW 2.1191 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Previous studies revealed that the spherical high molecular weight levan molecules produced by G. albidus TMW 2.1191 are functionally diverse regarding their hydrocolloid and rheological properties depending on their molecular size (Hundschell et al 2019(Hundschell et al , 2020Jakob et al 2012bJakob et al , 2013Ua-Arak et al 2016, 2017b. Moreover, the production pH during batch fermentation is crucial for the size distributions of these levans (Hundschell et al 2020;Ua-Arak et al 2017a) as also shown in the present work (Figs. 4,6).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Previous studies revealed that the spherical high molecular weight levan molecules produced by G. albidus TMW 2.1191 are functionally diverse regarding their hydrocolloid and rheological properties depending on their molecular size (Hundschell et al 2019(Hundschell et al , 2020Jakob et al 2012bJakob et al , 2013Ua-Arak et al 2016, 2017b. Moreover, the production pH during batch fermentation is crucial for the size distributions of these levans (Hundschell et al 2020;Ua-Arak et al 2017a) as also shown in the present work (Figs. 4,6).…”
Section: Discussionsupporting
confidence: 82%
“…or Bacillus subtilis (Natto) (Fels et al 2018;Jakob et al 2012a;Korakli et al 2003;Semjonovs et al 2016;Shih et al 2005;Xu et al 2006). The macromolecular or rather hydrocolloid properties of levan in aqueous solution mainly depend on its molecular weight and can be additionally influenced by its branching degree (at position O1) and polydispersity (Hundschell et al 2019(Hundschell et al , 2020Jakob et al 2012bJakob et al , 2013. However, it is unknown, which and if a certain amount, specific size and composition of levan is essential for survival or assertiveness of the producer strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one aim of the present study was to investigate these differences in more detail using rheological measurements. As reported in previous studies about microbial levans [37,45], the viscosity of these dextrans increased with rising molecular size despite comparable molecular structure and degree of branching (Table 2). Comparable thickening and gelling properties were reported for dextrans, which were linear and had a higher molecular weight than the dextrans investigated in the present study [58].…”
Section: Discussionsupporting
confidence: 82%
“…This usually results in the formation of diverse short-chain gluco-oligosaccharides that exhibit a low degree of polymerization and are promising prebiotics [30,[40][41][42][43]. The extreme differences in possible chain lengths contribute to the variable functional properties of the produced dextrans and other sucrase-derived EPSs [33,35,44,45] and can be controlled during production for the manufacture of tailor-made EPSs exhibiting the desired properties. By contrast, the structures and sizes of other commercially used plant-derived hydrocolloids such as cellulose or starch are comparably fixed, why they need to be synthetically modified to obtain varying hydrocolloid properties [46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%